Critical path of women in situation of violence: an integrative literature review - Jaqueline Arboit; Stela Maris de Mello Padoin; Cristiane Cardoso de Paula (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To identify Brazilian and international scientific evidence on the critical path of women in situations of violence. Method: Integrative literature review developed in four databases and two electronic portals, in January 2017. Twenty-one full articles in English, Portuguese or Spanish from original researches were included in the time cut from 1994 to 2016, and which presented critical path elements, even without using this concept. Results: The critical path of women in situations of violence is constituted of elements related to their perceptions, actions and previous experiences regarding availability and quality of services, social representations of public servers and community and the results obtained in the search for help. Conclusion: Critical path elements are decisive for the women, and can promote, inhibit or delay the beginning of the route and consequently the end of situations of violence experienced by these women.